Reciprocal Impact of Molnupiravir and Favipiravir Monocomponents of the Combination Drug on Each Other's Pharmacokinetics in a Phase I Clinical Trial - T. N. Komarov; K. K. Karnakova; N. S. Bagaeva; O. A. Archakova; M. O. Popova; V. S. Shcherbakova; K. Ya. Zaslavskaya; P. A. Bely; I. E. Shohin (Разработка и регистрация лекарственных средств)
Introduction. COVID-19 (Coronavirus disease 2019) almost 4 years after he start of the pandemic is still a significant public health problem. SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2) that causes COVID-19 continues to mutate and spread throughout the world. Molnupiravir and favipiravir have been shown to be efficacious against variety of RNA viruses including the SARS-CoV-2. The Ministry of Health of the Russian Federation approved the use of these drugs as a treatment of COVID-19. The developed drug contains the combination of two antiviral agents with different mechanisms of suppressing viral RNA replication, which suggests efficacy against the vast majority of ARVI pathogens found in the human population including SARS-CoV-2 and influenza.Aim. The aim of the pharmacokinetics study is comparison between JTBC00301 (INN: molnupiravir + favipiravir), film-coated tablets (LLC "PROMOMED RUS", Russia), Esperavir® (INN: molnupiravir), capsules (LLC "PROMOMED RUS", Russia) and Areplivir® (INN: favipiravir), film-coated tablets (LLC "PROMOMED RUS", Russia) to evaluate the impact of monocomponents on each other's pharmacokinetics.Materials and methods. The clinical and analytical phases as well as pharmacokinetic analyses have been performed as a part of a phase I, randomized, open-label, 3-period crossover study of drug JTBC00301 (INN: molnupiravir + favipiravir), film-coated tablets, 400 + 400 mg (LLC "PROMOMED RUS", Russia). The plasma concentration of β-D-N4-hydroxycytidine (NHC), the active metabolite of molnupiravir and favipiravir were determined in 42 healthy volunteers after taking the test drug JTBC00301 (1 tablet of 400 + 400 mg), the reference drug Esperavir® (2 capsules of 200 mg) and the reference drug Areplivir® (2 tablets of 200 mg). The descriptive statistics were calculated using Microsoft Excel (Microsoft Corporation, USA). The pharmacokinetic parameters, analysis of variance (ANOVA), the intra-subject coefficient of variation (CVintra) and 90 % confidence intervals (90 % CI) were calculated by R Project 3.5.1 software (package «bear», version 2.8.3-2), originally created by Hsin-ya Lee and Yung-jin Lee, Taiwan.Results and discussion. Pharmacokinetic parameters of NHC and favipiravir were determined, averaged pharmacokinetic profiles in linear and log-linear scales were plotted, analysis of variance was carried out. The 90% CIs for geometric mean ratios of Сmax and AUC(0–t) for NHC and favipiravir were all within the acceptance range of 80–125 % which means there is no effect of monocomponents on each other’s pharmacokinetics.Conclusion. The development of the fixed-dose drug combination of molnupiravir and favipiravir has great potential as it may allow to increase the safety profile and improve the tolerability of therapy as well as increase the effectiveness of antiviral therapy. The results justified the study of the subsequent phases of clinical trials of JTBC00301 (INN: molnupiravir + favipiravir), film-coated tablets, 400 + 400 mg (LLC "PROMOMED RUS", Russia).